Litigating religions : an essay on human rights, courts, and beliefs - McCrudden, Christopher (Oxford : Oxford University Press, 2018)
Human rights literature has tended to exclude religious foundations from the realm of human rights. This has led to a lack of progress which confuses our understanding of the relationship between human rights and religion: this work argues that by paying close attention to developments in human rights litigation we can make theoretical progress.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 20, 2018).
Keywords: Human rights -- Religious aspects; Religion; Religion & beliefs